2023
DOI: 10.3390/foods12112108
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Menthol, Eugenol and Their Combination against Aspergillus ochraceus and Aspergillus niger In Vitro and in Stored Cereals

Abstract: Aspergillus ochraceus and Aspergillus niger are spoilage and mycotoxin-producing fungi that can contaminate agricultural commodities and derived products. In the present study, menthol, eugenol, and their combination (mix 1:1) were tested to determine their contact and fumigation toxicity against the two fungi. Menthol, eugenol, and their mixture significantly reduced mycelial growth and spore germination at concentrations from 300 to 600 µg/mL, and the inhibitory effects showed clear dose dependence. The mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Ben Miri et al 55 reported sensitivity of Aspergillus ochraceus and A . niger to menthol and eugenol, common constituents derived from mint or myrtle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ben Miri et al 55 reported sensitivity of Aspergillus ochraceus and A . niger to menthol and eugenol, common constituents derived from mint or myrtle.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports also focus on reduction in aflatoxin synthesis, spore germination and mycelium growth of Aspergillus flavus under the influence of natural extracts (e.g. Shirazi thyme and cumin seed) 55 . In our research, natural extracts (lavender and marigold dry extracts; lavender, tea tree, clove and rosemary oils) caused an inhibition of Neosartorya sp.…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of these probably contaminated final products may pose a risk to the consumer and some studied samples were heavily contaminated with aflatoxins at levels higher than the limits prescribed by European Union (EU) regulations (4 μg/kg) (EU, 2010). The implications of aflatoxins go beyond the public health aspect but also commercial and economic ramifications ( Belasli et al 2023 ; Ben Miri et al 2023 ). Mitchell et al (2016) estimate that aflatoxin contamination could result in losses to the cereal industry up to US$1.68 billion per year in the United States (U.S.) due to climate change.…”
Section: Consumption Of Camel Meat and Health Risksmentioning
confidence: 99%
“…Although it is abundant in cloves ( Syzygium aromaticum ), it can also be found in various plants, giving them its typical pleasant odor and taste. The high value of this compound and its derivatives in the medicinal chemistry field is justified by its multifaceted activities, including its broad-spectrum antibacterial [ 7 , 8 ], antioxidant [ 9 , 10 ], antifungal [ 11 , 12 , 13 ], antiviral [ 14 , 15 , 16 ] and antiprotozoal [ 17 ] properties, among its many others [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%